Frequency Noise Characterization of a 25-GHz Diode-Pumped Mode-Locked Laser With Indirect Carrier-Envelope Offset Noise Assessment - Pierre Brochard; Valentin Johannes Wittwer; Slawomir Bilicki; Bojan Resan; Kurt John Weingarten; Stephane Schilt; Thomas Sudmeyer (IEEE Photonics Journal, 2018)
We present a detailed frequency noise characterization of an ultrafast diode-pumped solid-state laser operating at 25-GHz repetition rate. The laser is based on the gain material Er:Yb:glass and operates at a wavelength of 1.55 μm. Using a beating measurement with an ultralow-noise continuous-wave laser in combination with a dedicated electrical scheme, we measured the frequency noise properties of an optical mode of the 25-GHz laser, of its repetition rate and indirectly of its carrier-envelope offset (CEO) signal without detecting the CEO frequency by the standard approach of nonlinear interferometry. We observed a strong anticorrelation between the frequency noise of the indirect CEO signal and of the repetition rate in our laser, leading to optical modes with a linewidth below 300 kHz in the free-running laser (at 100-ms integration time), much narrower than the individual contributions of the carrier envelope offset and repetition rate. We explain this behavior by the presence of a fixed point located close to the optical carrier in the laser spectrum for the dominant noise source.